Application of Differentiated Learning through a Problem Based Learning Approach to Increase PkN Learning Activities for Students of Class IV MIN 1 Kerinci - Wisnarti, Wisnarti (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2023)
Low student learning activities need a strategy carried out by the teacher, this study aims to increase student learning activities in Civics subject the subject of Pancasila as the Value of Life. This study uses differentiated learning by implementing Problem Based Learning learning. This research is a classroom action research which is divided into two cycles. Each cycle consists of planning, implementing actions, observing, evaluating, and reflecting. The research was conducted on odd semester IV grade students at MIN 1 Kerinci for the 2022/2023 academic year with a total sample of 16 people. As for the results of the research conducted on 16 students, in pre-cycle activities the number of students who were in the active category were only 3 students (18.75%), while students who were less active were 13 students (81.25%), in cycle I students experienced an increase in the number of students who were active 7 students (43.75%) while students who were less active were 6 students (37.5%), and students who were quite active were 3 students (18.75%) Then in cycle II this experienced a very significant increase compared to the previous cycle, namely an increase in the number of students who were active, 13 students (81.25%) while there were no less active students and 3 students who were quite active (18.75%). This research shows that the application of differentiated learning by implementing Problem Based Learning learning can increase student activity in learning Civics on the subject of Pancasila as the Value of Life in odd semester grade IV at MIN 1 Kerinci in the 2022/2023 Academic Year